敗血症関連急性腎障害の治療に使用するための組み換えアルカリホスファターゼ (2022)
【課題】たとえば敗血症によって引き起こされる急性腎障害の症状の、予防、治療、治癒、または寛解のための、改良されたアルカリホスファターゼを提供する。【解決手段】治療が必要な対象における敗血症関連急性腎障害を治療するための方法であって、有効量のアルカリホスファターゼ（ＡＰ）を前記対象に投与することを含み、（ｉ）前記対象は、ＡＰによる治療前に６０ｍｌ／分以下のＥＣＣ（内因性クレアチニンクリアランス）量、またはＡＰによる治療前に６０ｍｌ／分以下のｅＧＦＲ（推定糸球体濾過量）を有し、（ｉｉ）前記ＡＰは、少なくとも５００Ｕ／ｋｇ～２，０００Ｕ／ｋｇの用量で投与され、（ｉｉｉ）前記ＡＰの投与は、腎機能の向上をもたらすことを特徴とする方法である。【選択図】なし The present disclosure relates to the use of alkaline phosphatases, and in particular improved alkaline phosphatases such as RecAP, for the prevention, treatment, cure, or amelioration of the symptoms of acute kidney injury caused, e.g., by sepsis. The application relates to methods of preserving renal function, shortening the duration of renal replacement therapy, increasing the creatinine clearance, decreasing the risk of death in subjects with sepsis-associate acute kidney injury (SA-AKI) or at risk of SA-AKI.